Foreign branches of US global banks: Geography, balance sheet structure and contagion - Carmela D'Avino (FIW - Research Centre International Economics, 2016)
This paper contributes to the understanding of the international financial linkages created by US banks by looking at the geographical composition and structure of the balance sheet of foreign branches. The empirical investigation, which is based on a novel dataset containing balance sheet statistics of foreign branches by country of location, has a threefold objective. First, it provides geographical mapping and distribution of foreign activities of branches by host country by accounting also for those balance sheet items not included in the available international banking statistics, i.e. gross interoffice positions and transactions with third-countries. Secondly, this paper presents a classification of host countries by balance sheet structure of foreign offices. A partioning-based clustering analysis allows to identify 4 distinct types of foreign branches: liquidity importers, liquidity exporters, liquidity conduits and locally implanted. Lastly, the paper provides evidence in support of the fact that US branches' banking foreign operations are a good measure of financial integration with US as they can significantly explain business cycle synchronisation between the host country and the US during the Great Recession.
Keywords: F33; F34; F36; F42; C23; C49; 330; US global banks; foreign branches; balance sheet structure; contagion